Time and frequency to observe fiducial markers in MLC-modulated fields during prostate IMRT/VMAT beam delivery. (August 2020) - Xu, Qianqian; Tong, Xu; Lin, Muhan; Chen, Xiaoming; ElDib, Ahmed; Lin, Teh; Chen, Lili; Ma, C-M Charlie
Highlights: IMRT/VMAT beam modulation affects fiducial visibility in EPID-based localization. The time and frequency to see fiducials in modulated fields were studied on DRRs. The visibility of gold fiducials on EPID was demonstrated using a pelvic phantom. A gold fiducial was visible during 40–70% beam-on time in prostate IMRT/VMAT. The time interval to see a gold fiducial was <10 s in prostate IMRT/VMAT. Abstract: Objective: This work investigates the time and frequency to observe fiducial markers in MLC-modulated fields during intensity-modulated radiotherapy (IMRT) and volumetric-modulated arc therapy (VMAT) beam delivery for real-time prostate localization. Methods: Thirty seven prostate patients treated with IMRT or VMAT were included in this retrospective study. DRR images were generated for all MLC segments/control points using the TPS. The MLC leaf pattern of each control point was overlaid on the DRR, and the number of fiducials within the MLC opening was analyzed. EPID images of fiducials in a pelvic phantom were obtained to demonstrate the fiducial visibility during modulated beam delivery. Results: Gold fiducials were visible on EPID images. The probability of seeing a number of fiducials within the MLC opening was analyzed. At least one fiducial was visible during 42 ± 2% and 52 ± 2% beam-on time for IMRT of the prostate with and without lymph nodes, and during 81 ± 4% and 80 ± 5% beam-on time for VMAT of the prostate with and without lymph nodes, respectively. The mean time interval to observe at least one fiducial was 8.4 ± 0.7 and 5.9 ± 0.5 s for IMRT of the prostate with and without the lymph nodes, respectively, and 1.6 ± 0.1 s for VMAT prostate patients. The estimated potential dosimetric uncertainty was 7% and 2% for IMRT and VMAT, respectively. Conclusions: Our results demonstrated that the time and frequency to observe fiducial markers in MLC-modulated fields during IMRT/VMAT beam delivery were adequate for real-time prostate localization. The beam's eye view fiducial positions could be used for intrafractional target monitoring and motion correction in prostate radiotherapy.